2006
DOI: 10.1074/jbc.m512305200
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Leukocyte Ig-like Receptor Signaling and Crystal Structure of Disulfide-linked HLA-G Dimer

Abstract: HLA-G is a nonclassical major histocompatibility complex class I (MHCI) molecule, which is expressed in trophoblasts and confers immunological tolerance in the maternal-fetal interface by binding to leukocyte Ig-like receptors (LILRs, also called as LIR/ILT/CD85) and CD8. HLA-G is expressed in disulfide-linked dimer form both in solution and at the cell surface. Interestingly, MHCI dimer formations have been involved in pathogenesis and T cell activation. The structure and receptor binding characteristics of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
238
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(249 citation statements)
references
References 53 publications
9
238
1
1
Order By: Relevance
“…Previous binding studies and structural reports of HLA-G proposed that the hydrophobic amino acids Phe-195 and Tyr-197 form hydrophobic interactions with LILRB1 and LILRB2 (4,5,14). The current structure clearly showed that Phe-195 is located close to the hydrophobic faces of Thr-48 and Ile-47 of LILRB2 and that Tyr-197 directly interacts with Arg-36 and Tyr-38 of LILRB2 ( Fig.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous binding studies and structural reports of HLA-G proposed that the hydrophobic amino acids Phe-195 and Tyr-197 form hydrophobic interactions with LILRB1 and LILRB2 (4,5,14). The current structure clearly showed that Phe-195 is located close to the hydrophobic faces of Thr-48 and Ile-47 of LILRB2 and that Tyr-197 directly interacts with Arg-36 and Tyr-38 of LILRB2 ( Fig.…”
Section: Resultsmentioning
confidence: 51%
“…In addition, HLA-G forms a disulfidelinked dimer in solution and at the cell surface (2,3). This dimer mediates much more efficient inhibitory signals than HLA-G monomers by binding to LILRB1 and LILRB2, as shown by cellular and biochemical studies (2)(3)(4). The recent crystal structures of the HLA-G monomer (5) and dimer (4) provided the structural basis for efficient signaling.…”
mentioning
confidence: 99%
“…However, HLA-G is unique among MHC I molecules, as it possesses an unpaired Cys 42 residue, situated on an external loop of the ␣1 domain, which allows it to form dimers (46). Such HLA-G dimers have been shown to be up to 100 times more efficient at LILRB1 signaling (47). Thus, it is possible that the exosomal MHC class I dimers we describe in this study may be potent ligands for recognition by NK lineage receptors biased toward HLA-A and -B molecules.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 also binds to HLA-G and competes with LILRB for binding to this site. These sites are readily accessible to receptors, explaining the increased avidity (26). However, no crystal structure of an HLA-G homodimer complexed with a LILRB protein has been published, although one for the HLA-G monomer-LILRB2 complex was reported (28).…”
mentioning
confidence: 99%
“…Previous reports clearly demonstrated that LILRB1 and LILRB2 preferentially bind to HLA-G relative to other classical class I MHC proteins such as HLA-A2 (25). HLA-G has a much higher affinity for LILRB1 than LILRB2 (26,27). A recent structural study showed that the HLA-G dimer binds with greater avidity to LILRB1/2 and signals more strongly through LILRB than monomeric HLA-G and other class I MHC proteins (25).…”
mentioning
confidence: 99%